KAJIAN LITERATUR: EFEKTIVITAS PELATIHAN DALAM ORGANISASI - Ubaidillah Ubaidillah (Universitas Batanghari, 2018)
This study discusses the role of training effectiveness, in improving employee performance towards the organization, the method used in this study is to look at theoretical theories related to the study of the impact and influence of training effectiveness on employee performance in the organization, the results of this study explain that training is applied to employees can have an effect on improving the ability and competence of employees, so that ultimately can affect the performance of employees in the organization.